OC-068 Measuring the Effect of Ispaghula on Gut Content and Function Using MRI. (17th August 2016) - Major, G; Murray, K; Nowak, A; Hoad, C; Kurtz, C; Silos-Santiago, A; Johnston, J; Marciani, L; Gowland, P; Spiller, R; ,
Abstract : Introduction: Ispaghula husk (IS) is believed to modulate functional gastrointestinal symptoms by drawing water into the bowel to soften stool and accelerate transit, and by adding bulk. It is not thought to be readily fermented. Magnetic Resonance Imaging (MRI) can assess gastrointestinal content and function. The aim of the study was to assess whether MRI could detect and quantify the effects of IS in patients with chronic constipation. Methods: A double-blind crossover study in adults with functional constipation or constipation-predominant irritable bowel syndrome. Intervention: Metamucil Original Coarse Fibre® (P&G, USA) 14 g tds – daily IS dose 21 g. Placebo: Maltodextrin(MD) 14 g tds. On day 5 subjects swallowed 5 gadolinium filled capsules. On day 6 MRI scans were taken fasting and hourly for 7 hours while subjects ingested a rice pudding meal and treatment (IS or MD). Whole gut transit was assessed by the weighted average position score of the capsules 24 hours after ingestion (WAPS). Free water in the small bowel (SBWC) and ascending colon (ACWC) was measured as were T1 and T2 relaxation times in the ascending and descending colon (AC & DC), colonic volume and gas. Results: 16 subjects completed both treatments. Transit was faster after IS with a mean decrease in WAPS of 24% (p = 0.05, 1 tailed). Postprandial SBWC was markedly higher on IS (p < 0.001) with smaller increases seen in ACWC (p < 0.05). Fasting T1 was significantly higher after IS in both AC and DC. T2 fasting values were also higher. A postprandial rise was seen in both T1 AC and T2 AC after IS but not MD. Fasting colonic volume increased on PS by mean 332 mL or 48%. Exploratory analysis of colonic gas found that after IS significantly more was detectable both fasting (p < 0.05) and postprandially (p < 0.05). AC gas did not increase until 240 min after PS while transverse colon gas increased steadily through the day. Conclusion: MRI parameters demonstrated accelerated in transit, increased intestinal water content and increasedcolonic volume with IS. Fasting T1 appears to discriminate constipation from health and responded to treatment. More colonic gas was detected with IS. This may reflect fermentation of IS or interference with small bowel absorption leading to malabsorption of carbohydrate in the rice meal. These novel findings illustrate the potential for MRI to provide insights into the in vivo effects and mechanisms of action of gut modulators. Disclosure of Interest: None Declared